Official monitoring of Brazil’s native vegetation using satellite images: the BiomasBR program and the Prodes, Deter and TerraClass systems - Almeida, Cláudio Aparecido de; Perez, Letícia Palazzi; Reis, Mariane Souza; Camilotti , Vagner Luis; Messias, Cassiano Gustavo; Monteiro, Erison Carlos dos Santos; Pinheiro, Taise Farias; Sobrinho Kneipp Cerqueira Pinto, João Felipe; Soler, Luciana de Souza; Vinhas, Lubia; Maurano, Luis Eduardo Pinheiro; Adami, Marcos; et al. (Cadernos de Astronomia, 2025)
The Brazilian government has three official satellite monitoring systems for monitoring native vegetation loss in its six biomes, designed and executed by the National Institute for Space Research, through the Brazilian Biomes Monitoring Program (BiomasBR): 1) Prodes - Annual Monitoring of Native Vegetation Suppression; 2) Deter - Daily Monitoring of Suppression and Degradation of Native Vegetation; and 3) TerraClass - Systematic Monitoring of Land Cover and Use. This article presents the main characteristics of each of these systems, the most recent results of Brazilian native vegetation monitoring, the main public policies based on BiomasBR, and the role of the program as a tool for achieving goals within international climate agreements.